Clinical and microbiological evaluation of non-surgical periodontal therapy in obese and non-obese individuals with periodontitis: a 9-month prospective longitudinal study (Journal of Applied Oral Science, 2021)
Objective: Obesity is a chronic disease that negatively affects an individual’s general and oral health. The present study aimed to compare the clinical and microbiological effects of non-surgical periodontal therapy with the full mouth disinfection (FMD) protocol on obese and non-obese individuals at 9 months post-therapy. Methodology: This clinical study was first submitted and approved by the Ethics Committee. Fifty-five obese patients and 39 non-obese patients with periodontitis were evaluated. The full-mouth periodontal clinical parameters, clinical attachment level (CAL), probing depth (PD), gingival index (GI), and plaque index (PI), were monitored at baseline, 3, 6, and 9 months after periodontal treatment with full mouth disinfection (FMD) protocol. The mean count of Tannerella forsythia , Porphyromonas gingivalis , Treponema Denticola , and Aggregatibacter actinomycetemcomitans was determined by quantitative polymerase chain reaction on subgingival biofilm samples. Demographic data were assessed by Chi-square test. For clinical and microbiological parameters, two-factor repeated-measures ANOVA was used. Results: In both groups, periodontal therapy using the one-stage full-mouth disinfection protocol significantly improved CAL, PD, GI, and PI (p<0.05). Obese and non-obese patients equally responded to non-surgical periodontal therapy (p>0.05). Microbial count found no major differences (p>0.05) between obese and non-obese individuals who had undergone non-surgical periodontal therapy. Conclusions: Obesity did not affect the clinical and microbiological outcomes of non-surgical periodontal therapy.